2021
DOI: 10.1101/2021.01.30.428937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surviving hypothermia by ferritin-mediated iron detoxification

Abstract: SUMMARYHow animals rewire cellular programs to survive cold is a fascinating problem with potential biomedical implications, ranging from emergency medicine to space travel. Studying a hibernation-like response in the free-living nematode Caenorhabditis elegans, we uncovered a regulatory axis that enhances the natural resistance of nematodes to severe cold. This axis involves conserved transcription factors, DAF-16/FoxO and PQM-1, which jointly promote cold survival by upregulating FTN-1, a protein related to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 77 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…These results are consistent with the silencing of ets-4 by both proteins. However, we noticed that the extend of cold survival appears to differ between the rege-1(-) ; ets-4(-) and rle-1(-) ; ets-4(-) double mutants, with the former surviving cold even better than wild type (21). It indicates that, in addition to ets-4 co-regulation, RLE-1 and/or REGE-1 may play other roles that do not require their cooperation.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…These results are consistent with the silencing of ets-4 by both proteins. However, we noticed that the extend of cold survival appears to differ between the rege-1(-) ; ets-4(-) and rle-1(-) ; ets-4(-) double mutants, with the former surviving cold even better than wild type (21). It indicates that, in addition to ets-4 co-regulation, RLE-1 and/or REGE-1 may play other roles that do not require their cooperation.…”
Section: Resultsmentioning
confidence: 84%
“…We previously showed that REGE-1 facilitates the accumulation of body fat and cold resistance by lowering the levels of ETS-4 (Fig. 1A) (14,21). Because RLE-1, like REGE-1, is required for the silencing of ets-4 mRNA, one could expect similar biological functions of both proteins.…”
Section: Rle-1 and Rege-1 Have Overlapping Biological Functionsmentioning
confidence: 91%
See 1 more Smart Citation